Manipulating the Acoustic Characteristics of Kenaf as a Sound Absorber by Modifying the Thickness and Air Gap - Abdul Khalid, Mohamad Syahmi Haziq; Nor Azali bin Azmir,; Shahmir Hayyan bin Sanusi, (International Journal of Integrated Engineering, 2024)
The purpose of this study is to provide a better understanding of the material properties of kenaf fibre from the National Kenaf and Tobacco Board (NKTB) and investigate the performance of kenaf fibre as a material for sound absorption. Non-woven kenaf fibre from the NKTB is a material made from the fibres of the kenaf plant that is processed into a non-woven form. The fabricated samples were made of 65% kenaf fibre and 35% Bico (Polyester) as the binder. Non-Woven kenaf fibre is produced using a Thermo-bonding machine and through several mechanized processes. Bico (Polyester) will act as a low melt synthetic fibre that is melted during the Thermo-bonding process to attach the kenaf fibre. The acoustical properties involved several components, namely the sound absorption coefficient and noise reduction coefficient. It has been indicated that the sound absorption coefficient and noise reduction value for sample 50 mm at middle range frequency (500 Hz-1000 Hz) can be improved by increasing the thickness and air gap. At the end of the study, a comparison of acoustical performance between kenaf fibre properties for sound absorption. The results demonstrated that the performance of kenaf fibre was comparable with another material. This shows that kenaf fibre has a big potential to be made as an alternative material for sound absorber. This research provides knowledge on the acoustical properties of kenaf fibre that contribute to the consumption of natural fibre as biodegradable, environmentally friendly, safe, and cost-efficient.